PENERAPAN PENDEKATAN KONTEKSTUAL DALAM MENINGKATKAN HASIL BELAJAR MATA PELAJARAN EDITING VIDEO PADA SISWA PRODUKSI SIARAN PROGRAM TELEVISI SEKOLAH MENENGAH KEJURUAN NEGERI 1 BLITAR - Wardhana, Aditya Kusuma (TARBAWI:Journal on Islamic Education, 2023)
Video Editing in Vocational High School is expected to be a vehicle for students to learn about themselves and the natural surroundings. For this reason, Learning emphasizes providing direct learning experiences. One of the learning methods that can be applied is the contextual approach which emphasizes the full involvement of students to be able to find the material being studied and relate it to real life situations. This research approach uses a qualitative approach with the type of Classroom Action Research (CAR). The data source in this action research was Eleven grade vocational high school in Blitar. Data collection methods: (1) Test, (2) Observation, (3) Interview, (4) Field notes. Analysis model: The data analysis used is a flow model (1) data reduction, (2) presenting data, (3) drawing conclusions. The results of the study show that Video Editing learning with a contextual approach can improve student learning outcomes. This is shown by the student learning outcomes in the first cycle test the average student obtained was 75.2 and then in the second cycle the average obtained was 83.4 Based on the research results, it can be concluded that learning Video Editing using a contextual approach can improve student learning outcomes